Mini review: possible role of the multi-theory model of health behavior change in designing substance use prevention and treatment interventions - Sharma, Manoj; Awan, Asma; Kapukotuwa, Sidath (Frontiers in Public Health, 2024)
Many behavior change theories have evolved over time. Originally, the first conceptions prioritized interventions based on information, such as raising awareness and transferring knowledge. Second-generation theories prioritize the development of skills and the promotion of awareness. The emergence of evidence-based techniques in the 1990s gave rise to third-generation theories such as the Theory of Planned Behavior and Social Cognitive Theory. Presently, fourth-generation trends amalgamate various components from multiple theories to implement accurate treatments, employing technology and emphasizing targeted behavior change. This paper aims to do a concise evaluation of the multi-theory model (MTM) of health behavior change interventions in the context of planning substance use prevention and treatment. the current area of intervention programs aimed at preventing and treating substance use may benefit from MTM, an innovative fourth-generation behavior change model. Tobacco, alcohol, and other drugs have all been the subjects of experimental, cross-sectional, and qualitative research. We have presented that additional research is required to compare MTM with knowledge-based therapies or interventions grounded in other theories. A gold standard would be the randomized controlled trials and behavioral change interventions particularly useful for this purpose. In addition, research evaluating the interventions' efficacy must be carefully planned and executed.